Theoretical fundament modifications performed in the evaluation system at the Internal Medicine ward round performance. - Luis Alberto Corona Martínez; Juan Rivero Berovides (Medisur)
The medical clinic department in the medicine school located in Cienfuegos city, Cuba performed modifications to the evaluation system in the subject Internal Medicine during the academic course 1999-2000. The main ideas are shown in this investigation constituting the theoretical backgrounds of the changes performed due to the identified deficiencies found and based on the actual pedagogical concepts and acceptation. It is emphasized on the need that the whole system of evaluation should be pertinent, productive, wide, profound, and conformed by the diversity of instruments, so that its instructive, educative, oriented, motivated, and feedback functions should be accomplished.